Pembuatan Sediaan Gel Arang Tempurung Kelapa Dan Uji Daya Hambat Terhadap Bakteri Klebsiella pneumoniae: Preparation of Coconut Shell Charcoal Gel and Inhibitory Test Against Klebsiella pneumoniae Bacteria - Kamalah, Siti Rahmah; Kurniawan, Kurniawan; Mulyanto, Arif; Dhanti, Kurnia Ritma (Borneo Journal of Medical Laboratory Technology, 2023)
Klebsiella pneumoniae is a gram-negative rod-shaped bacterium that is a member of the Enterobacteriaceae group of bacteria and is pathogenic and can infect humans. Currently, many K. pneumoniae bacteria are resistant to antibiotics, giving rise to new problems in the health sector that must be addressed immediately by utilizing biodiversity in the form of medicinal plants such as coconut trees, which can produce coconut shells that can be made into charcoal. The results of the phytochemical analysis show that coconut shell charcoal contains many active compounds that have been used in the cosmetic and health industries. The purpose of this study was to obtain an optimal and effective coconut shell charcoal extract gel formula for inhibiting the growth of K. pneumoniae bacteria. This study included a true experimental post-only control group with different gel concentration groups, namely 3%, 6%, and 9%. The optimal formulation of coconut shell charcoal extract gel is a gel with a concentration of 9%, and the results of the one-way ANOVA statistical analysis show that the treatment of the inhibition test on K. pneumoniae bacteria from gels with different concentrations shows that there is a mean difference in the area of the inhibition zone with a significant value of 0.033 (p<0.05). The results of the LSD post-hoc test showed that several treatment groups had significant values (p <0.05). Based on the results of the study, it can be concluded that the optimal formulation of shell charcoal extract gel is a gel with a concentration of 9%, while the most effective gel for inhibiting the growth of K. pneumoniae bacteria is a gel with a concentration of 3%.